Molecular mechanism of mitoquinol mesylate in mitigating the progression of hepatocellular carcinoma—in silico and in vivo studies - Sulaimon, Lateef Adegboyega; Adisa, Rahmat Adetutu; Titilola, Aderonke Samuel (Wiley, 2021)
The safety and efficacy of mitoquinol mesylate (MitoQ) in attenuating the progression of hepatocellular carcinoma (HCC) in Wistar rats has been reported. However, the binding modes for MitoQ as well as its molecular mechanisms in cirrhosis and liver cancer have not been fully investigated. This study sought to understand the structural and molecular mechanisms of MitoQ in modulating the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and mitochondrial succinate dehydrogenase (SDH) in cirrhotic-HCC rats. The research indicates that the upregulated Nrf2 expression in cirrhotic-HCC rats was significantly (p < 0.05) reduced by MitoQ while the activity of SDH was significantly (p < 0.05) increased. Analysis of binding modes revealed MitoQ interacts with amino acid residues in the active pocket of tramtrack and bric-a-brac (BTB) and KELCH domains of KEAP1 with average binding affinities of −66.46 and −74.74 kcal/mol, respectively. Also, MitoQ interacted with the key amino acid residues at the active site of mitochondrial complex II with a higher average binding affinity of −75.76 kcal/mol compared to co-crystallized ligand of complex II (−62.31 kcal/mol). Molecular dynamics simulations data showed the binding of MitoQ to be stable with low eigenvalues while the quantum mechanics calculations suggest MitoQ to be very reactive with its mechanism of chemical reactivity to be via electrophilic reactions. Thus, MitoQ modulates expression of Nrf2 and enhances activity of mitochondrial SDH in cirrhotic-HCC rats via its interaction with key amino acid residues in the active pocket of BTB and KELCH domains of KEAP1 as well as amino residues at the active site of SDH. These findings are significant in demonstrating the potential of Nrf2 and SDH as possible biomarkers for the diagnosis and/or prognosis of hepatocellular carcinoma in patients. This study also supports repurposing of mitoQ for the treatment/management of liver cirrhosis and HCC.
Keywords: mitoquinol mesylate; in silico; Ireoluwa Yinka Joel; Akinrinade George Ayankojo; University of Lagos; ACE: Drug Research, Herbal Medicine Development and Regulatory Science; ACEDHARS